Teachers’ Classroom Management in SMK Telkom 2 Medan - Roy Dedi Ansarika Ginting (elt, 2019)
Abstract This study was aimed to investigate teachers’ classroom management in teaching learning process. The research was done in SMK Telkom 2 Medan. The period of observing the teachers’ classroom management was a week. The research’s participants of this study were the teachers in SMK Telkom 2 Medan. The instruments used in this research was observation. Based on the data analysis in the research, researcher found that the classroom management used by the teachers in SMK Telkom 2 were the exact moment of the lesson in which the teacher starts teaching, the locations of special needs students during the class period, use of rewards-punishment for special needs students and other students, use of individualized care for special needs students and the degree of effective use of classroom period.